Radiofrequency waves increase the brain levels of inflammatory biomarkers, neurotrophin and serotonin - Azimzadeh, Mansour; Radmard, Fatemeh; Jelodar, Gholamali (Neurotak Publishing, 2024)
The increase in mobile technology has raised concerns about the potential health effects of mobile phone radiation. The biological impact of exposure to radiofrequency (RF) waves emitted by electronic devices has been extensively studied and is a concern for the public, policymakers, and health researchers. The study aimed to examine the impact of 900 MHz radiofrequency waves on biomarkers such as interleukin (IL)-1α, IL-1β, tumour necrosis factor (TNF)-α, homocysteine, nerve growth factor, and serotonin in rats' serum and brain tissue. Thirty adult male Sprague Dawley rats (200 ± 20g) were randomly assigned to three groups (n=10): control (not exposed to RF), exposed I (2 hours per day), and exposed II (4 hours per day). The exposed groups were exposed to 900 MHz RFW for 30 consecutive days. The results showed that only the exposed group II significantly increased serum serotonin levels compared to the control group (P=0.0496). IL-1α, TNF-α, and nerve growth factor levels in brain tissue increased significantly in both exposed groups compared to the control group (P<0.0001). The control group had significantly lower levels of IL-1β compared to exposed groups I (P=0.0289) and II (P=0.0004). Additionally, serotonin and homocysteine levels in the brains of exposed II were significantly higher compared to the other groups (P<0.0001). The results showed disruptions in all biomarkers, indicating the potential impacts of daily exposure to 900 MHz radiofrequency waves from mobile phones on brain function. This suggests that mobile phone radiation may affect brain function.